The coloured Jones polynomial, the Chern–Simons invariant, and the Reidemeister torsion of the figure‐eight knot. (14th December 2012) - Murakami, Hitoshi
Abstract : We show that from the asymptotic behaviour of an evaluation of the coloured Jones polynomial of the figure‐eight knot we can extract the Chern–Simons invariant and the twisted Reidemeister torsion associated with a representation of the fundamental group of the knot complement to the two‐dimensional complex special linear group.